miRNA accumulation correlates with increased phloem cell proliferation in tomato hawaiian skirt mutants - Lombardo, Fabien; El mestari, Tarek; Kirat, Thomas; Jondah, Muhammad Ijaaz; Marsaudon, Julie; Bollier, Norbert; Mastukura, Chiaki (Frontiers in Plant Science, 2025)
IntroductionThe cambium is the meristem responsible for production of plant vascular tissues, the xylem (wood) and phloem, during plant radial growth. Due to its internal location and relatively low cell number, the biology of the cambium remains less well understood compared to other plant meristems. The tomato hws mutant exhibits miRNA accumulation and produces a markedly enlarged phloem, suggesting a role for miRNAs in regulating vascular development. This study aims to identify the accumulated miRNAs associated with the vascular phenotype in hws mutants and characterize their impact on phloem development kinetics.MethodsTo achieve this, we analyzed the vascular phenotype of hws mutants using pedicel and stem sections examined using light and scanning electron microscopy, alongside RNA sequencing of miRNAs from pedicels.ResultsOur findings reveal increased cell division rates during the phloem expansion phase in hws-1 while xylem is reduced due to a shortened expansion phase in pedicels. Key miRNAs, including miR319 and miR164, were identified as highly accumulated in the mutant pedicels. Vascular phenotypes in stems were consistent with those observed in pedicels.DiscussionOur findings underscore the potential for manipulating miRNA levels to improve phloem capacity and possibly crop yields through targeted genetic strategies.